2005
DOI: 10.1093/bja/aei045
|View full text |Cite
|
Sign up to set email alerts
|

Size 2 ProSeal™ laryngeal mask airway: a randomized, crossover investigation with the standard laryngeal mask airway in paediatric patients

Abstract: The size 2 PLMA offered some advantages over the same size of SLMA in this crossover investigation. The high reliability of gastric tube placement and the significantly increased airway leak pressure might have important implications for use of this device for positive pressure ventilation in infants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

27
77
8
3

Year Published

2005
2005
2013
2013

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 67 publications
(115 citation statements)
references
References 22 publications
27
77
8
3
Order By: Relevance
“…Our data on neutral OLP values and, commensurately, our V T max values for the air-Q ILA are lower than existing published data for the PLMA. [2][3][4]14 Our findings for air-Q ILA sizes 1.5 and 2.0 are similar to those previously published, 10,11 where the mean (standard deviation [SD]) OLP was 17.5 (6.4) cm H 2 O and 18.5 (1.6) cm H 2 O for size 1.5 and 15.7 (4.3) cm H 2 O for size 2.0. Our OLP findings for size 1 were higher than those by Sinha et al 11 who reported a mean (SD) OLP of 18.5 (2.1) cm H 2 O. Oropharyngeal leak pressures increase when the patient's neck is in the flexed position, a phenomenon also described with the PLMA.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Our data on neutral OLP values and, commensurately, our V T max values for the air-Q ILA are lower than existing published data for the PLMA. [2][3][4]14 Our findings for air-Q ILA sizes 1.5 and 2.0 are similar to those previously published, 10,11 where the mean (standard deviation [SD]) OLP was 17.5 (6.4) cm H 2 O and 18.5 (1.6) cm H 2 O for size 1.5 and 15.7 (4.3) cm H 2 O for size 2.0. Our OLP findings for size 1 were higher than those by Sinha et al 11 who reported a mean (SD) OLP of 18.5 (2.1) cm H 2 O. Oropharyngeal leak pressures increase when the patient's neck is in the flexed position, a phenomenon also described with the PLMA.…”
Section: Discussionsupporting
confidence: 90%
“…Previously published studies of performance of new iterations of LMAs in adults and children have used similar group sizes. [2][3][4] Data are described with median [P25,P75] for continuous data and frequency (percent) for discrete and categorical data. Due to its observational design, this study was not powered for comparisons, and as such, no inferential methods of statistical analysis were employed.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a bench study fluid was injected into a model esophagus: at 15 mL·sec -1 the PLMA prevented aspiration; at 30 mL·sec -1 , or with the DT occluded, protection was reduced but better than the cLMA. 51 In ten fresh cadavers with a PLMA in place and the DT open, incremental filling of the esophagus did not cause tracheal soiling. 53 The PLMA provided better airway protection during 'regurgitation' than the cLMA.…”
Section: Airway Protection Gastric Inflation Regurgitation and Aspimentioning
confidence: 87%
“…The PLMA was associated with a higher seal pressure and maximum tidal volume, less gastric inflation and improved laryngeal view compared to the cLMA. 51 In another study of 60 children: insertion, airway seal and fibreoptic view were all equivalent. 52 OGT passage was successful in all patients in both studies.…”
Section: Plma Use In Childrenmentioning
confidence: 95%